1899 Wyo. Rev. Stat. 600, div. 1, tit. 15, ch. 1, § 2106 - (:unkn) unknown (My University, 1899)
No person or persons shall ensnare, net or trap within this state any wild duck, wild goose, or wild swan at any time. . . . There shall be established from the first day of September until the first day of May, an open season in which ducks, brant or geese may be shot, killed or taken by means of gun shot, but nothing but shoulder guns may be used at any time. And it shall be unlawful to kill any of the above mentioned water fowls by any other means, or during any other period, than above specified; Provided That it shall be unlawful for any person or persons to kill any wild swan in the state of Wyoming. Any person or persons who shall violate the provisions of this section shall be deemed guilty of a misdemeanor, and upon conviction thereof, shall be fined not less than ten nor more than twenty-five dollars for each offense, and may be imprisoned in the county jail for not more than sixty days.
Keywords: HUNTING REGULATION